The frequency of nodular gastritis in adult patients and the relation of this type of gastritis with Helicobacter pylori and histopathologic findings - Yalaki, Serkan (The European Research Journal, 2019)
Objectives: Endoscopic nodular gastritis is usually used to describe the miliary nodular appearance of the gastric mucosa during endoscopy. Recent studies have shown that nodular gastritis is closely related to Helicobacter pylori (H. pylori) infection and may cause stomach cancer, especially in young women. We aimed to determine the frequency of nodüler gastritis in this study, other lesions seen during endoscopy, H. pylori frequency and histopathological findings.Methods: Adult patients who underwent endoscopy between March 2015 and April 2017 were identified. Medical records of patients; demographic characteristics, endoscopic features and pathologic were investigated retrospectively. Patients with nodular gastritis were compared with age and gender matched control group.Results: Of the 1877 patients evaluated, 39 patients with endoscopic nodular gastritis and 72 as control group were enrolled. The prevalence of H. pylori infection was significantly higher in patients with endoscopic nodular gastritis than in the control group (74.35% versus 63.88%, p < 0.0001). The most common concurrent endoscopic findings were erosions (25.64%). Histopathologically, the prevalence of atrophic gastritis and intestinal metaplasia in the patients with endoscopic nodular gastritis was also higher than in the control group (p < 0.05). Conclusions: Nodular gastritis is often caused by chronic H. pylori infection. It is observed more frequently in women and children. Most patients with H. pylori infection have no specific symptom or complication, but some patients may develop premalign conditions such as active gastritis, atrophic gastritis and intestinal metaplasia. For this reason, H. pylori eradication in patients with nodular gastritis may reduce the development of peptic ulcer and possibly gastric malignancy.